Pengaruh Pemberian Ekstrak Daun Kelor Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri di SMP Neg 3 Tinambung Tahun 2022 - Irmayanti AR (LPPM STIKES Marendeng Majene, 2023)
the Effect of Moringa Leaf Extract Administrasion on the Increase of Hemoglobin Content in Young Girls In SMP Neg 3 Tinambung in 2022. This study aimed at: (1) determining the dose of moringa leaf extract administrasion on the increase of hemoglobin content in the the group of adolescent administrated moringa leaf extract at SMP Neg 3 Tinambung, (2) determining the frequency of moringa leaf extract administration on the increase of hemoglobin content in the group of adolescent administrated moringa leaves at SMP Neg 3 Tinambung. This study used quasy experimental method by pretest – posttest experimental design with control group design. The sample size in this research is 66 adolescents. The results showed that the change of pre of post hemoglobin content in the highest intervention group is that the young girls (female students) who experienced the increase of hemoglobin content amount to 33 girls sig value. 0,000 or P<0,05 which means that there is influence of education and moringa extract administration at SMP Neg 3 Tinambung. The difference of pre/post hemoglobin content in control group with sig value 0,733 or P>0,005 which means that there is no effect of education on the increase of hemoglobin content in female adolescent (female student) at SMP Neg 3 Tinambung. Or we can also say that in the control group, there is no significant difference, consumption of moringa leaf extract at the dose of 1000 mg with 2x daily consumption frequency for 2 months in adolescent girls can incease hemoglobin content significantly p<0,05.